2019
DOI: 10.1016/j.ebiom.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced wound healing promotion by immune response-free monkey autologous iPSCs and exosomes vs. their allogeneic counterparts

Abstract: Comparing non-inbred autologous and allogeneic induced pluripotent stem cells (iPSCs) and their secreted subcellular products among non-human primates is critical for choosing optimal iPSC products for human clinical trials. Methods: iPSCs were induced from skin fibroblastic cells of adult male rhesus macaques belonging to four unrelated consanguineous families. Teratoma generativity, host immune response, and skin wound healing promotion were evaluated subsequently. Findings: All autologous, but no allogeneic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
3
48
0
Order By: Relevance
“…We have previously demonstrated that iPSCs transplanted onto skin wounds in monkeys accelerate the wound healing by promoting epithelial recovery, angiogenesis, and collagen deposition through paracrine signaling and differentiating into endothelial cells. Further, autologous monkey iPSCs were more effective than allogeneic iPSCs in promoting would healing [6]. Taken together, our results demonstrate that reducing the immunogenicity of allogeneic (and, in our case, even xenogenic) stem cells can improve stem cell therapy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We have previously demonstrated that iPSCs transplanted onto skin wounds in monkeys accelerate the wound healing by promoting epithelial recovery, angiogenesis, and collagen deposition through paracrine signaling and differentiating into endothelial cells. Further, autologous monkey iPSCs were more effective than allogeneic iPSCs in promoting would healing [6]. Taken together, our results demonstrate that reducing the immunogenicity of allogeneic (and, in our case, even xenogenic) stem cells can improve stem cell therapy.…”
Section: Discussionsupporting
confidence: 58%
“…Patient safety is a priority in effective stem cell therapy. The bottleneck issues challenging stem cell application include unwanted differentiation [ 1 , 2 ], stem cell thrombosis [ 3 5 ], transplant-recipient immunogenicity [ 6 , 7 ], and integration failure [ 8 ]. Besides, there is a dilemma regarding the time, workload, and economic burden of individualized autologous iPSC generation and immune rejection of allogeneic iPSCs and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Although iPSCs and their derivatives have been demonstrated to be effective for myocardial repair, the teratogenic risk of these cells remains a concern and limits the routine clinical uses of these cells (Ben-David and Benvenisty, 2011;Zhao et al, 2011). Several studies had shown that iPSCs indeed form teratoma in mice and non-human primates (Zhao et al, 2011;Hong et al, 2016;Lu et al, 2019). iPSC-derived exosomes may possess unique advantage in this regard.…”
Section: Teratogenic Potential Of Ipsc Exosomesmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) arrays are based on probe binding and can detect changes in a genome with higher resolution (kb) than G-banding (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This method enables us to study copy number variations (CNVs), >20% mosaicism and loss of heterozygosity (LOH) but on the other hand, it is unable to detect <20% mosaicism, balanced chromosomal translocations, and inversions [30].…”
Section: Single Nucleotide Polymorphismmentioning
confidence: 99%
“…While some discuss the use of undifferentiated hiPSCs as a therapy product [18,19], the majority of hPSCs applications assume their directed differentiation before use, since undifferentiated cells can pose a risk of tumorigenicity. Many different cell types have been generated from hPSCs and some have already been used in clinical trials.…”
Section: Introductionmentioning
confidence: 99%